Core components for an ai literacy curriculum: proposing the metamorphic framework for augmented intelligence - Antypenko, L.; Antypenko, O. M.; Антипенко, Олексій Миколайович (My University, 2025)
Aim. Drawing from recent research and implementation data, the proposed framework aims to provide structured guidance for educational contexts from early education to organizational settings.